Correction: Multiple noncovalent interaction constructed polymeric supramolecular crystals: recognition of butyl viologen by para-dicyclohexanocucurbit[6]uril and α, α′, δ, δ′-tetramethylcucurbit[6]uril. Issue 2 (25th October 2017) - Xiao, Zhi-You; Lin, Rui-Lian; Tao, Zhu; Liu, Qing-Yun; Liu, Jing-Xin; Xiao, Xin
Abstract : Correction for 'Multiple noncovalent interaction constructed polymeric supramolecular crystals: recognition of butyl viologen by para -dicyclohexanocucurbit[6]uril and α, α′, δ, δ′-tetramethylcucurbit[6]uril' by Zhi-You Xiao et al., Org. Chem. Front., 2017, DOI: 10.1039/c7qo00708f.